Dielectric and optical properties of lead-borotellurite glass system - Mustafa, Iskandar Shahrim (2011)
Homogeneous ternary (Te02)y [(PbO)x (B203)I-xh-y glass system (x = 0.0 - 0.50 and y = 0.7) were successfully synthesized using a conventional melt-quenching method. The glasses were then irradiated at different doses from 5 kGy up to 25 kGy with intervals of 5 kGy with 1.33-MeV gamma rays at a constant dose rate of 3.167 kGy/hours produced by 60Co radionuc1ide. The effect of dose variation and composition of PbO on the dielectric, optical, physical and structural properties of the PbO-B203-Te02 glass has been studied. Generally, the increase in the density is related to the high dense PbO (9350 kg/rrr') compared to that of Te02 (5670 kg/rrr'). This change in density by the addition ofPbO is also related to the change in the atomic mass and atomic volume .of constituent elements. Furthermore, the observed increase in density ofTe02-PbO-B203 glasses as irradiated with gamma ray is due to a tightening effect or compaction of the glass structure. The XRD diffractograms shows that all the glasses prepared are partially crystalline as the ,amount of PbO increased in the glass network. Furthermore, all the glass prepared proved to fit amorphous state as the irradiation dose increases. The addition of heavy metal oxide modifiers to pure Te02 leads to the progressive formation of distorted Te03+I polyhedron followed by the creation of regular trigonal Te03 pyramids that contain non-bridging oxygen. PbO stands out as unique substance because of its dual role (i) as modifier, if Pb-O is ionic (ii) as glass former with Pb04 structural units, if Pb-O is covalent. Based on the Raman spectra results, the increase broad shoulders at 410 ern" indicate that new features to vibrations of one of the partially crystalline phase of Pb3Te06. The existence of Pb3Te06 is confirmed by X-ray analysis. The change in Tg indicates a change related to the manner in which PbO gets arranged in the glass. Eventually, the decrease in the glass transition temperature implies a decrease in the rigidity of the network due to addition amount of network intermediate PbO. The glass transition temperature increases with increasing of radiation dose which designate changes of the glass structure. The optical absorption spectra of the glasses were measured and the Urbach rule has been applied to evaluate the fundamental absorption edges for all the glasses from the obtained spectrum. The optical band gaps were calculated from the absorption edge and it was found that the .optical band gap energy, Eopt depended on the glass composition and irradiation exposure. The dielectric permittivity is known as the polarizability of the material under external electric field whiles the dielectric loss is contributed to the energy loss during polarization process. The results of dielectric response measurements show that electrode polarization at low frequency, orientation polarization at intermediate frequency and polarization of defect glass structure at high frequency are the most probable process responsible for the observed dielectric behaviour of the studied glass samples. The peaks are also clearly observed within the imaginary part of the electrical modulus, M" as a function of frequency at different temperature. Activation energy are observed to decrease with simultaneous successive increase in PbO concentration of (Te02)y [(PbO)x (B203kx)l-y glasses and irradiation dose. The reasons for such changes may be due to gradual increase in the fraction of octahedrally positioned lead ions in the glass network which act as modifiers. These ions weaken the glass network and create pathways suitable for migration of free ions that build up space charge. Thus, the weaker the network, the more is the space charge polarization, leading to an increase in the dielectric parameters. The phenomenon is supported by (i) decrease in the glass transition temperature Tg and related parameters with PbO concentration, (ii) the splitting of Te-O- Te and B-O-B bonds in the Raman spectra and (iii) decrease in the value of optical band gap, Eopt.